The long-term labor market effects of parental unemployment - Bernhard Schmidpeter (W.E. Upjohn Institute for Employment Research, 2020)
I investigate the impact of parental unemployment on children's educational attainment and long-run labor market outcomes in Austria. I find that parental unemployment shortly before an important educational decision by parents for their children lowers a child's probability of holding a university degree by more than 5 percentage points. I do not find that income is affected at the beginning of a child's labor market career along the distribution, but I find a gradual deterioration later on. A substantial share of these long-term losses can be explained by the lower parental investment decision. My results emphasize the intergenerational and long-lasting consequences of parental unemployment.
Keywords: C21; I23; J13; J31; J64; 330; parental unemployment; intergenerational effects; long-term effects; unemployment; wage loss; decomposition